WŁADYSŁAW TARNAWSKI AS A SCHOLAR OF ENGLISH LITERATURE - Budrewicz, Aleksandra (Prace Polonistyczne, 2022)
The article examines the achievement of Władysław Tarnawski (1885–1951), a Polish translator and scholar who specialized in English literature. It discusses Tarnawski’s biography, his political and aesthetic views, as well as contribution to English studies in Poland and the Polish reception of British literature and its translations. The author also analyses the criteria which Tarnawski adopted in order to evaluate the works of British writers and the way he expressed his opinions thereof. Tarnawski’s views and assessment criteria were deeply rooted in Polish politics and history of the first half of the twentieth century.